Va rooog ajutatima!!! 2•[2+2•(2^3-2^5:2^3)]+3•2^2
Răspunsuri la întrebare
Răspuns de
1
2×[2+2×(2^3-2^5:2^3)]+3×2^2
=
=2×[2+2×(2^3-2^2)]+12 =
=2×[2+2×2^2(2^1-2^0)]+12=
=2×[2+2×2^2(2-1)]+12 =
=2×[2+2×2^2]+12 =
=2×[2+8]+12 =
=20+12=32
=2×[2+2×(2^3-2^2)]+12 =
=2×[2+2×2^2(2^1-2^0)]+12=
=2×[2+2×2^2(2-1)]+12 =
=2×[2+2×2^2]+12 =
=2×[2+8]+12 =
=20+12=32
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă